(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the main problems in the development of the hydropower sector in Khorezm region. The natural and geographical features of the region, dependence on the Amudarya, outdated infrastructure, distribution of water resources and the negative impact of climate change on hydropower production are considered on a scientific basis. Also, the importance of small and micro-hydropower plants, obstacles to their implementation and proposals for solutions to these problems are given.